Strengthening Cooperation among Intelligence Agencies in the Enforcement of Law on Terrorism: The Case of Indonesia - Rizki Wahyudi; Muhammad Syauqillah (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2022)
The development of global, regional and national situations related to terrorism is dynamic and complex affecting national stability and security. It requires optimal and effective action from the government. The complexity of counter-terrorism requires the synergy of all parties. Strengthening cooperation between intelligence agencies can solve the current threat of terrorism. This article aims to propose intelligence cooperation and present the concept of intelligence synergy within the framework of law enforcement in combating terrorism in Indonesia. The article is descriptive qualitative research. It employs in-depth interviews and literature study as a data-gathering technique. Using collaborative governance theory, the article argues that to realize synergy between intelligence agencies, all Indonesian intelligence agencies need to conduct joint action procedures and hold joint terrorism countermeasures exercises, and related activities aimed at creating a common perception and eliminating rivalry among the agencies.